Comparison of Performance of an Intermittent Aeration Membrane Bioreactor and a Conventional Activated–sludge System in the Treatment of Palm Oil Mill Effluent - Annop, S.; Sridang, P.; Chevakidagarn, P.; Nopthavorn, K. (Journal of Applied Membrane Science & Technology, 2017)
The main objective was to compare the performances and the removal efficiencies of two biological treatment systems, a submerged membrane bioreactor (SMBR) and a simultaneous activated sludge (AS), for treating Palm Oil Mill Effluent (POME). Two lab scale units of SMBR and AS with a working volume of 24 L were operated under favorable biological conditions and minimized membrane fouling intensity. To achieve both carbonaceous and nitrogen removal, the cyclic air intermittent and dissolved oxygen control were performed into SMBR and AS with the influent flow rate about 16 L/d respectively. In terms of organic removal and membrane performance, the SMBR showed good removal efficiency to treat high strength wastewater with organic loading variation of POME. The average removal rates of TCOD, BOD, Turbidity, Color, Oil and Grease, NH3–N, TKN were 69±2, 76±2, 100±1, 37±21, 92±6, 67±4 and 75±10% respectively. Results pointed out the benefit of membranes retained totally the active compositions of biomass in each stage of development. The AS showed the limitation of sedimentation phase for sludge and oil separation. The characteristics of sludge in SMBR showed healthy floc formations and good settling after 240 h. The concentrations of COD and BOD in permeate were around 870±53 and 37±13 mg/L.